Analysis of the correlation between clinical nurses' professional quality of life and family care and organizational support - Xu, Shan; Ju, Dandan; Chen, Ye; Wu, Meiliyang; Wang, Lan; Xi, Xinxue; Zeng, Tieying (Frontiers in Public Health, 2023)
Background and aim： Nurses' professional quality of life (ProQOL) is closely related to nursing life, and it is essential to clarify the professional quality of life of nurses and enhance it effectively. We aimed to explore the influence of family care and organizational support on the professional quality of life of clinical nurses and to improve the theoretical basis for improving the professional quality of life of clinical nurses in China. Methods: A single center, descriptive, cross-sectional design was used in this study. From February to April 2022, 2200 nurses from Tongji Hospital were selected as the study population, using the General Information Form, Family Care Scale, Professional Quality of Life Scale, Nurses' Sense of Organizational Support Questionnaire, and Work-Family Conflict Scale, and analyzing the relationship between professional quality of life and family care and organizational support among clinical nurses for correlation analysis as well as multiple linear regression to determine the factors affecting participants' Factors affecting ProQOL. p < 0.05 values were considered statistically significant. Results: The Cronbach coefficients of the scales were generally above 0.8, with good validity. All nurses had empathic satisfaction, burnout, and secondary trauma scores of 28.74±3.83, 30.82±3.45 and 29.40±3.69, respectively, and correlation analysis, as well as multiple linear regression results, showed that the three dimensions of nurses' professional quality of life were associated with family care and organizational support (p< 0.05). Conclusions: The professional quality of life of nurses deserves to draw focused attention. The degree of family care and organizational support are predictive of professional quality of life, and nursing managers should pay attention to rationalizing tasks, pay attention to the physical and mental health of nursing staff, and improve the quality of life of nurses.